Factors Related To Delivery Place Selection Among Pregnant Women In Jambi In 2020 - Nia Ike Lestari; Shinta Novelia; Anni Suciawati (Universitas STRADA Indonesia, 2020)
This study aims to determine the factors related to the choice of delivery place. This research is an analytic survey research with cross sectional design. The sampling technique in this study was conducted with a total sampling method of 108 pregnant women. Data was collected using a questionnaire that had been tested for validity and reliability and was processed with the Chi-Square statistical test. The results showed that 61.1% of pregnant women chosed non-health facilities (home) in the selection of labor, then the statistical test found a significant relationship between economic status / income (ρ value = 0.008) and husband / family support (ρ value = 0.005 ) with the delivery place selection, other factors not related delivery place selection are education (ρ value = 0.231), knowledge (ρ value = 0.826) and distance (ρ value = 0.099).